The past in the past in the mortuary practice of hunter-gatherers: an example from a settlement and cemetery site in northern Latvia - Lars Olof Georg Larsson (Documenta Praehistorica, 2017)
During excavations of burials at Zvejnieki in northern Latvia, it transpired that the grave fill included occupation material brought to the grave. It contained tools of a type that could not be contemporaneous with the grave. This is confirmed by the dating of bone tools and other bone finds in the fill. The fill was taken from an older settlement site a short distance away. The fill also included skeletal parts of humans whose graves had been destroyed with the digging of the grave for a double burial. This provides an interesting view of the mortuary practice of hunter-gatherers and an insight into the use of the past in the past.